Baccaurea Lour. (Phyllanthaceae Martinov - Malpighiales), underutilized plant from Riau, Indonesia and its phytochemical study (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Sofiyanti N, Fitmawati, Isda MN, Agesti ARA, Sari M, Pranata S. 2022. Baccaurea Lour. (Phyllanthaceae Martinov-Malpighiales), underutilized plant from Riau, Indonesia and its phytochemical study. Biodiversitas 23: 937-946. Baccaurea (Phyllantaceae) is one of underutilized plants in Riau Province, Indonesia. Our finding in some districts shows the variation of morphological characters of Baccaurea members. However, there is no detailed morphological study of these genera reported from this province. This study aimed to identify Baccaurea species from Riau and characterized their morphology, as well as, phytochemical contents. The specimens were collected from the field, documented and observed in detail their morphological characters. Phytochemical screening had been conducted using qualitative tests of a total of six secondary metabolites (alkaloid, terpenoid, steroid, tannin, flavonoid and saponin). A total of seven Baccaurea species were identified in this study. The main characteristic that can be used to distinguish each species are leaf characteristics (venation, size and shape), floral pattern and fruit characters. The phytochemical contents vary among the examined Baccaurea. Steroid and tannin are absent from all of examined specimens. Terpenoid is commonly found in all fruit parts of all specimens.  The result of this study provides the first detailed morphological record as well as phytochemical data of Baccaurea from Riau.